Age Group With Severity Scales And Functional Status Carpal Tunnel Syndrome On Elderly At Nursing Home Santo Yosef Surabaya - Liong, Andryano; Dian, Teuku Arief; Djuari, Lilik (FAKULTAS KEDOKTERAN UNIVERSITAS KATOLIK WIDYA MANDALA SURABAYA, 2020)
Introduction: Carpal tunnel syndrome (CTS) is a condition which is known as one of the cumulative trauma disorder (CTD) that can happen to the wrist or arm with a symptoms like pain, loss of sensitivity, weakness, and tingling that commonly occur to the thumb, index finger and middle finger. Prevalence of CTS that has been reported keep increasing each year, up to 276/100.000 cases each year. Aim: The aim of this research is to know if there’s a correlation between age group and carpal tunnel syndrome symptom on elderly at nursing home Santo Yosef Surabaya. Methods: This research use observational study with analytic design and the method that’s used in this research is cross sectional. Analysis in this research will be using spearman correlation test to know the correlation between variables. The population in this research is 154 elderly at the senior home facility Santo Yosef Surabaya. There is 70 elderly for this research sample. Results: From the analytic result, it has been found that the symptom severity (SSS) and age group and functional status (FSS) and age group is significant with the p score of p =0.0017 and p= 0.049 respectively, from the data that’s acquired from the result of spearman test it can be also concluded that from the coefficient correlation score of r=0.284 there’s a weak correlation between severity symptom (SSS) and age group, the correlation score of r=0.236 from the functional status (FSS) and age group indicate that it also have a weak correlation power. Conclusion: In conclusion, there was a significant correlation between age group and severity symptom in CTS (SSS). There is a significant correlation between age group and functional status in CTS (FSS).